1986
DOI: 10.1051/jphys:019860047070124900
|View full text |Cite
|
Sign up to set email alerts
|

X-ray method for the structural investigation of thin organic films

Abstract: Résumé. 2014 Nous montrons que la simple conjugaison de trois techniques conventionnelles de rayons X permet une étude structurale des films minces lamellaires. La diffraction en transmission du rayonnement synchrotron fournit une détermination de l'arrangement intra-lamellaire, la diffraction en réflexion à petits angles, celle de l'ordre inter-lamellaire et enfin la réflexion critique donne une mesure de la densité nécessaire à l'obtention du nombre d'unités structurales par maille. Nous présentons une illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…26). This observation confirms our former X-ray experiments which showed that each layer is made of microdomains separated by grain boundaries [2]. Note that such holes have been also observed in dense packed phospholipid monolayers [5].…”
supporting
confidence: 91%
“…26). This observation confirms our former X-ray experiments which showed that each layer is made of microdomains separated by grain boundaries [2]. Note that such holes have been also observed in dense packed phospholipid monolayers [5].…”
supporting
confidence: 91%
“…From a theoretical point of view, very interesting systems involving polar molecules with high dipole moments should give rise to complex phase diagrams in which a supercrystal phase is expected [2]. In all cases the knowledge of the structure of the layer will be necessary to help fully understand these systems [3].…”
Section: Physics Abstractsmentioning
confidence: 99%
“…Among them X-ray reflectometry has gained much favor, and high-resolution X-ray reflectometers are now commonplace apparatus. For example, alumina or mica foils have already been used [3]. It is possible to obtain in-plane information in the reflective mode using grazing angle X-ray diffraction [2].…”
Section: Introductionmentioning
confidence: 99%